Kampung Eduwisata Hanjeli di Desa Waluran Mandiri Kabupaten Sukabumi - Setiawan, Iwan Rizal; Isa, Indra Griha Tofik; Hestiana, Siska; Tsani, Ashrul (University of Merdeka Malang, 2020)
Land use of Waluran Mandiri Village, which consists of agricultural land and rice fields, has the potential to increase the economy of the people in the area. However, this was not matched by the custom of local people who preferred to be gold miners, known as â€œGurandilâ€. Some of the commodities that can be developed in this area are Hanjeli beans. The purpose of this activity is to involve the community in developing the potential of hanjeli beans which are packaged in the Hanjeli edutourism village. The stages carried out in this activity were the initial workshop, community counseling, the formation of a group discussion forum, the revitalization of agricultural land, the making of a blueprint for the eduwisata Hanjeli edutourism village, and the final workshop. The final result of this activity is a blueprint of Hanjeli edutourism village which consists of budget design, educational spots, educational layouts (layout and spatial layout), the various arts involved and consolidation of the residents' land used.DOI:Â https://doi.org/10.26905/abdimas.v5i3.4382Â